Implementasi Metode Qiroati untuk Meningkatkan Kemampuan Membaca Al-Quran Kelas VII di MTs Al-Falah - Nasikhatul Umah; Nur Rodiatul Munawaroh; Siti Ayisah; Siti Fatimah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The Qiro'ati method is used at MTs Al Falah, therefore this research was conducted under the title Implementation of the Qiraati Method to Improve Class VII Quran Reading Ability in 2023 at MTs Al Falah. This study aims to examine students' ability to read the Koran. The purpose of this study was to determine students' ability to read the Koran through the qiro'ati method in class VII Mts Al-Falah. While the benefits that can be drawn from this research are for information materials for teachers and insights for researchers. This type of research is classroom action research. In this study, researchers will describe the application of the qiro'ati method to improve students' reading of the Koran. The location in that is at Mts Al-Falah with research subjects namely class VII students, totaling 25 students. Data collection techniques used are observation, interviews, documentation, and tests. The results of the study can be concluded that learning the Koran with the qiro'ati method has a significant experience at each meeting. In the first cycle there was an increase, namely at the second meeting 40% to 56%.